Photoinduced melting of antiferromagnetic order in La(0.5)Sr(1.5)MnO4 measured using ultrafast resonant soft x-ray diffraction. - Ehrke, H; Tobey, R; Wall, S; Cavill, SA; Först, M; Khanna, V; Garl, T; Stojanovic, N; Prabhakaran, D; Boothroyd, A; Gensch, M; Mirone, A; et al. (2011)
We used ultrafast resonant soft x-ray diffraction to probe the picosecond dynamics of spin and orbital order in La(0.5)Sr(1.5)MnO(4) after photoexcitation with a femtosecond pulse of 1.5 eV radiation. Complete melting of antiferromagnetic spin order is evidenced by the disappearance of a (1/4,1/4,1/2) diffraction peak. On the other hand, the (1/4,1/4,0) diffraction peak, reflecting orbital order, is only partially reduced. We interpret the results as evidence of destabilization in the short-range exchange pattern with no significant relaxation of the long-range Jahn-Teller distortions. Cluster calculations are used to analyze different possible magnetically ordered states in the long-lived metastable phase. Nonthermal coupling between light and magnetism emerges as a primary aspect of photoinduced phase transitions in manganites.